2020
DOI: 10.3390/ijerph17093152
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Aggression and Burnout in Nursing—The Moderating Role of Follow-Up Counseling

Abstract: The aim of this study is to obtain a better understanding of the association between the frequency of nurses’ exposure to workplace aggression from patients and their levels of burnout. In particular, we seek to shed light on the role of the availability of follow-up counseling in organizations after critical incidents in mitigating the adverse relationships between physical and verbal aggression and nurses’ burnout. A total of 582 nurses reported how frequently they had experienced physical and verbal aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…According to some studies, it was shown that WV decreased significantly when using this method [ 88 ]. In that sense, it is important to note that workplace violence is one of the possible causes of burnout in the health sector [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies, it was shown that WV decreased significantly when using this method [ 88 ]. In that sense, it is important to note that workplace violence is one of the possible causes of burnout in the health sector [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding violence, 69% of the cases are episodes involving patients. 3 Some studies 4,5 have highlighted that violence in healthcare services mainly affects workers who are responsible for the first direct communication with patients and their families, i.e., Nursing professionals, making them more vulnerable. Research in other countries has indicated that, among health professionals, the highest prevalence of episodes of violence involves nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Research in other countries has indicated that, among health professionals, the highest prevalence of episodes of violence involves nurses. 4,6,7 The frequent experience of exposure contributes to the severity of the problem, since workers are frequent victims of this phenomenon, potentially in the Family Health Strategy (FHS). 8,9 Among the health scenarios in Brazil, the FHS stands out as the main model of Primary Health Care (PHC) in the country and an important service in the context of the Unified Health System (UHS).…”
Section: Introductionmentioning
confidence: 99%
“…Although, the nurse could bear moderate to severe levels of burnout, but still the nurse performance tended to increase when the high level of positive psychological capital and communication skill have been embedded in the nurse. Hence, it needed to develop a customized and/or strategies that were concerned on the realization of positive psychological capital and provide several levels of burnout intervention for nurses, so it could maintain and/or improve the nursing performance outcomes (Vincent-Höper et al, 2020).…”
Section: Communicationmentioning
confidence: 99%
“…A research done by Vincent-Hoper, et al (2020) has found that the availability of follow-up counseling program in an organization was able to decline the relationship between physical assault and three burnout dimensions. Furthermore, the results also recommended that the follow-up counseling should be available for the nurses, since it could help reducing negative impacts on nurse mental health from the assault action taken by the patient (Vincent-Höper et al, 2020).…”
Section: Communicationmentioning
confidence: 99%